Music as an implementation strategy for evidence-based health interventions in Africa: a systematic review using the RE-AIM framework - Chidi Okafor; Shravya Allena; Olufunto A. Olusanya; Ucheoma Nwaozuru; Ifedola Olojo; Amenze Eguavoen; Njideka Okubadejo; Rajesh Vedanthan; Collins Airhihenbuwa; Olajide Williams; Olugbenga G. Ogedegbe; David Oladele; et al. (Implementation Science Communications)
Abstract Background While a growing body of scientific literature suggests that evidence-based interventions may improve health outcomes in diverse settings, little is known about the best strategies for large-scale implementation. In Africa, music—an important positive social determinant of health—leverages existing cultural values, which may effectively enhance the reach, uptake, and long-term sustainability of evidence-based interventions in the region. To understand how music interventions work, why they are effective, and with whom they resonate, this systematic review aims to evaluate the quality and empirical application of music as an implementation strategy for adopting evidence-based interventions in Africa using the RE-AIM framework as a guide. Methods A comprehensive librarian-assisted search followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Five major electronic databases, EBSCOhost, PubMed, Web of Science, Embase, and MEDLINE, were searched for empirical studies focused on using music as an implementation strategy to improve health outcomes in Africa. Two independent investigators extracted components of retrieved papers using the RE-AIM framework as a guide. Results From 981 citations, eight studies met the inclusion criteria, each reporting a unique music intervention. The interventions were conducted in West Africa (n = 3), South African regions (n = 4), and East Africa (n = 1) and included seven observational studies and one randomized controlled trial (RCT). Using the RE-AIM scoring criteria, we summarize the RE-AIM dimensions reported from selected studies – Adoption (72.5%) being the highest, followed by Reach (62.5%), Implementation (41.7%), and Efficacy/Effectiveness (20.0%). All eight studies (100%) described the intervention location, the expertise of delivery agents, the target population, and the participant characteristics. Moreover, our analysis highlighted the effectiveness of music interventions in enhancing health outcomes, particularly in improving knowledge and awareness (62.5%), facilitating behavioral change (50%), and promoting mental health (25%). Conclusion Music interventions adapted to the sociocultural context in Africa have the potential to help prevent diseases, improve well-being, and enhance health outcomes. Our review emphasizes the importance of customizing music-based interventions to fit the cultural context, which can enhance the programs' effectiveness, acceptance, and sustainability. Clinical trials are necessary to confirm the efficacy of music interventions in specific medical conditions and from a public health promotion perspective.